2016
DOI: 10.1016/j.bmcl.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a stable and orally bioavailable englerin analogue

Abstract: Synthesis of analogues of englerin A with a reduced propensity for hydrolysis of the glycolate moiety led to a compound which possessed the renal cancer cell selectivity of the parent and was orally bioavailable in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…was determined with the new formulation; however, on intravenous administration, doses decreasing to 0.1 mg/kg were immediately lethal. 52 The extreme intravenous lethality is consistent with data reported by the Novartis group, while the Novartis workers were unable to deliver 1 by the intraperitoneal route, even at doses as low as 1 mg/kg. Note that a Cremophor emulsion was used by Novartis.…”
Section: Preclinical Studiessupporting
confidence: 87%
See 3 more Smart Citations
“…was determined with the new formulation; however, on intravenous administration, doses decreasing to 0.1 mg/kg were immediately lethal. 52 The extreme intravenous lethality is consistent with data reported by the Novartis group, while the Novartis workers were unable to deliver 1 by the intraperitoneal route, even at doses as low as 1 mg/kg. Note that a Cremophor emulsion was used by Novartis.…”
Section: Preclinical Studiessupporting
confidence: 87%
“…50 Conversion to a glycolamide shows some promise, but the low intrinsic activity this series has shown so far is puzzling. 52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently approved treatments for renal cell carcinoma are of limited efficacy and are often toxic. Therefore, there has been keen interest in the discovery of (−)-EA and methods for its synthesis (25). A larger screen revealed that (−)-EA kills cells from a wide range of lineages but again supported the absence of adverse effects on normal, non-cancerous cells (6).…”
Section: Introductionmentioning
confidence: 99%